Rewarding conservative politicians? Evidence from voting on same-sex marriage - Björn Kauder; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We examine whether voters rewarded conservative politicians who were voting in favor of same-sex marriage. Data is based on a roll-call vote in the German national parliament (Bundestag) in June 2017. This roll-call vote drastically influenced the public discourse about the social political platform of the conservative party. National elections took place in September 2017. The results show that the vote share of conservative politicians who voted in favor of same-sex marriage was around 1.29 percentage points (around 0.33 standard deviations of the change in the first vote share) higher than the vote share of conservative politicians who did not vote in favor of same-sex marriage. Voters were seeking for outcomes other than economic outcomes to evaluate politicians' performance in office.
Keywords: D72; D78; P16; 330; Rewarding and punishing politicians; conservative politicians; roll-call votes; same-sex marriage; economic voting